Inflammatory bowel disease and risk of Parkinson’s disease: evidence from a meta-analysis of 14 studies involving more than 13.4 million individuals - Li, Hong-xing; Zhang, Cui; Zhang, Kai; Liu, Yi-zhe; Peng, Xiao-xiao; Zong, Qiang (Frontiers in Medicine, 2023)
Background: The relationship between inflammatory bowel disease (IBD) and the risk of Parkinson’s Disease (PD) has been investigated in several epidemiological studies. However, the results of these studies were inconclusive and inconsistent. We evaluated the potential relationship between IBD and PD risk by a meta-analysis. Methods: Search the electronic databases PubMed, Embase and Cochrane databases from inception to November 30, 2022, to identify relevant studies that assess the risk of PD in patients with IBD. The cohort, cross-sectional, mendelian randomization and case-control studies that reported risk estimates of PD and IBD were included in our analysis. The random-effect model and fixed-effects model were used to calculate the summary relative risks (RRs) with 95% confidence intervals (CIs). Results: 14 studies (nine cohort studies, two cross-sectional studies, two mendelian randomization studies and one case-control study) involving more than 13.4 million individuals were analyzed in our analysis. Our results suggested that the risk of PD in IBD patients is moderately increased, with the pooled RR was 1.17 (95% CI: 1.03-1.33, P = 0.019). Omit of any single study from this analysis had little effect on the combined risk estimate. No evidence of publication bias was found. In the subgroup analysis, the combined RR was 1.04 (95% CI: 0.96, 1.12, P = 0.311) for Crohn’s disease (CD), and 1.18 (95% CI: 1.06, 1.31, P = 0.002) for ulcerative colitis (UC). In addition, a significant association was identified in patients with IBD aged ≥ 60 years (RR = 1.22; 95% CI: 1.06-1.41, P = 0.007), but not in age < 60 years (RR=1.19; 95% CI: 0.58-2.41, P = 0.639). Meanwhile, the meta-analysis results suggested a protective role for IBD medication use against PD development, with the RR was 0.88 (95% CI: 0.74, 1.04, P = 0.126). Conclusion: Our results indicated that patients with IBD had a moderately higher risk of PD compared to non-IBD individuals. Patients with IBD should be aware of the potential risks for PD, especially who were ≥ 60 years old.